First get rid of n/2, so you would multiply 2/n on both sides: 2/n(S)=[(2/n)(n/2)],these will cancel out and you will be left with(A+t)
2/n(S)= (A+t)
-t -t
Subtract t on both sides to get A alone
2/n(S)-t=A so this is what a equals
S = n/2(A+t) solve for A
I don't undersand what to do with all these variables.
6 answers
pretend the others are just numbers (that's all they are anyway)
S = n/2(A+t) , multiply each side by 2
2S = n(A+t) , expand
2S = nA + nt, you want to get the A term alone
2S - nt = nA , divide both sides by n
(2S - nT)/t = A
S = n/2(A+t) , multiply each side by 2
2S = n(A+t) , expand
2S = nA + nt, you want to get the A term alone
2S - nt = nA , divide both sides by n
(2S - nT)/t = A
last line should say
(2S - nt)/n = A
(2S - nt)/n = A
he right i made a mistake , and oh he made the correction
Your both wrong. The answer is A=2S/n-t
How?